The importance of the Malacca Straits to Japan: cooperation and contributions toward littoral States - Noraini Zulkifli,; Sharifah Munirah Alatas,; Zarina Othman, (Penerbit UKM, 2014)
Due to the Malacca Straits’ strategic centrality in contemporary regional shipping routes, the Japanese have become very concerned about the passage of ships through the area as they have increasingly attracted the attention of maritime criminals such as pirates and smugglers. This study has two objectives, namely to 1) describe the background and the importance of the Malacca Straits to Japan; 2) discuss Japan’s contribution and its cooperation with the littoral states. Significantly, this study has found that, in order for Japan to protect its own national interests, it has had to take the necessary steps to strengthen diplomatic relations with littoral states as well as assisting in improving maritime security in the Malacca Straits. Based on empirical evidence, this study proposes several approaches toward improve current regional cooperation mechanisms by addressing common regional security issues.